MENGHADAPI FENOMENA KERUSAKAN DI MUKA BUMI (KAJIAN LAFADZ FASAD DALAM Q.S AR-RUM: 41) - Zidni Alfani Rizkiyah; Dian Erwanto (CV. Adiba Aisha Amira, 2023)
The choice of the theme of facade or in Indonesian means damage in this study departs from the reality that there has been a lot of damage in the environment around us in particular, and in all parts of the world in general. Both in the form of physical and non-physical damage. And the majority of scholars' refer to Q.S ar-Rum (30) verse 41 in the discussion of damage, because the text regarding the spread of damage on earth is summarized in Q.S ar-Rum (30) paragraph 41. Then to assist the research process this writer uses a type of literary research with tahlili approach or analysis that refers to the interpretation in the book of tafsir al-Mishbah by M. Quraish Shihab. This study seeks to review the meaning of lafadz fasa as a whole and comprehensively, also accompanied by an explanation of the division of fasaad, namely in the form of hissi facade or physical and meaningful or non- physical in nature, supplemented by examples. Then examine the contents of Q.S ar-Rum (30) verse 41 by grouping them into four sections which are considered to have a unified discussion and then summarized in one scheme. This research can at least provide some findings, including: 1) the meaning of lafadz fasaad and its examples, 2) offering a solution, namely al-islah which can be an endeavor to improve the world, 3) there is an impact or retribution as a result of acts of damage and accompanied by with some examples, 5) wisdom behind God's vengeance to the perpetrators of damage.